CAPAIAN DAN RESPON SISWA SMP NEGERI FAVORIT DI KOTA SUKABUMI MELALUI SOAL TRENDS IN INTERNATIONAL MATHEMATICS AND SCIENCE STUDY (TIMSS) - Suhendar Suhendar; Ayi Wahyuni (Biosfer: Jurnal Pendidikan Biologi, 2018)
The research is aimed to know student achievement and teacher response on TIMSS. The research method used is descriptive. This achievement is captured the TIMSS questions in 2007 and 2011 on the ecosystem concept. The test contains 20 questions consisting of 14 essays and 6 multiple choice questions. The TIMSS questions also consist of several cognitive domains of knowing, applying and reasoning. Responses of students and teachers were collected through questionnaires and interviews. The study subjects are class VIII B 1 of School A and class VIII E School B 2 of Sukabumi in the academic year of 2015/2016. The results show that average achievement in School A is in the poor category (41%) and School B is in the fair category (56%). The achievements based on cognitive domain, 80% for knowing the domain, 43% for applying domain and 53% reasoning domain. Some students of School A and most of the students of School B feel interested in TIMSS problem, while the teachers think that TIMSS questions will be used if it already familiar.